Novel penicillin-resistant clones of Streptococcus pneumoniae in the Czech Republic and in Slovakia - Figueiredo, A M; Austrian, R; Urbaskova, P; Teixeira, L A; Tomasz, A (Microbial drug resistance (Larchmont, N.Y.), 1995)
Seventy-two penicillin-resistant Streptococcus pneumoniae isolates collected from clinical specimens in the Czech and Slovakian Republics between 1990 and 1992 were analyzed by a variety of molecular techniques. Most of the highly resistant isolates (40/72) (penicillin MIC between 1 up to 16 micrograms/ml) were represented by two distinct pneumococcal clones, and most of these isolates (35/40) were also resistant to at least two other antibiotics (tetracycline plus chloramphenicol or erythromycin). All 17 isolates belonging to the first clone were of serotype 14, had very high penicillin MICs (8-12 micrograms/ml), shared a common, abnormal penicillin-binding protein (PBP) pattern and one of two related pulsed-field gel electrophoretic (PFGE) patterns. The 15 isolates belonging to the second clone were all of serotype 19A, had penicillin MICs between 1 and 4 micrograms/ml, shared a unique, abnormal PBP pattern, and could be divided into two subgroups on the basis of PFGE patterns, one of which was indistinguishable from the PFGE pattern of a multiresistant capsular type 19A clone of S. pneumoniae already identified earlier in Hungary. Thirty-two of the 72 pneumococcal isolates had lower penicillin MICs (0.1-0.5 microgram/ml), and these isolates differed from the more highly resistant ones in several respects: They belonged to seven different serotypes, showed large variation in PFGE patterns (20 patterns in 32 isolates) and most of them (21/32) were resistant to penicillin only. Tentative explanations for these findings, in terms of epidemiological and molecular mechanisms, are considered.
Keywords: Slovakia; Slovenská republika; Bacterial Proteins; Pneumococcal Infections; karboxypeptidasatranspeptidasa; Česká republika; Penicillin-Binding Proteins; Hexosyltransferases; peptidyltransferasy; Czech Republic; Carrier Proteins; Peptidyl Transferases; proteiny vázající penicilin; lidé; Humans; bakteriální proteiny; Streptococcus pneumoniae; pneumokokové infekce; rezistence na penicilin; Muramoylpentapeptide Carboxypeptidase; transportní proteiny; Penicillin Resistance; hexosyltransferasy